The Determinants of Financial Statement Fraud: Fraud Pentagon Perspective - Jannah Zahra Inayah; Anis Chariri (Universitas Negeri Malang, 2024)
Purpose: This study investigates the determinants of financial statement fraud from the perspectives of fraud pentagon theory. It is important to study the issue within the context of state-owned companies (BUMN) as stakeholders pay a lot of attention on the companies.Method: This research is quantitative one, with a logistic regression analysis of the 16 BUMN's financial statements listed on the Indonesian Stock Exchanges for the period of five years (2018-2022). The F-Score model is adopted to measure the indications of fraudulent statement of the companies.Findings: The findings show that the five components of fraud pentagon theory do not fully determine the the indication of fraudulent financial statements of the companies. Only financial targets (FT) and CEO duality (CEOD) show significant values with negative relationship. This implies that on the context of BUMN, the five components of fraud pentagon theory do not play important roles in triggering fraudulent financial statements.Originality/Value:This paper stands out for being one of the few studies analyzing the arrogance component of fraud Pentagon theory using CEO duality. Most of previous studies on Pentagon fraud utilize CEO photographs to represent arrogance and result in inconsistent findings. Thus this paper extends current studies on the importance of using CEO duality as a proxy of arrogance.